The Onecut Transcription Factor HNF-6 Regulates in Motor Neurons the Formation of the Neuromuscular Junctions - Audouard, Emilie; Schakman, Olivier; René, Frédérique; Huettl, Rosa-Eva; Huber, Andrea B.; Loeffler, Jean-Philippe; Gailly, Philippe; Clotman, Frédéric (PLOS ONE, 2012)
The neuromuscular junctions are the specialized synapses whereby spinal motor neurons control the contraction of skeletal muscles. The formation of the neuromuscular junctions is controlled by a complex interplay of multiple mechanisms coordinately activated in motor nerve terminals and in their target myotubes. However, the transcriptional regulators that control in motor neurons the genetic programs involved in neuromuscular junction development remain unknown. Here, we provide evidence that the Onecut transcription factor HNF-6 regulates in motor neurons the formation of the neuromuscular junctions. Indeed, adult Hnf6 mutant mice exhibit hindlimb muscle weakness and abnormal locomotion. This results from defects of hindlimb neuromuscular junctions characterized by an abnormal morphology and defective localization of the synaptic vesicle protein synaptophysin at the motor nerve terminals. These defects are consequences of altered and delayed formation of the neuromuscular junctions in newborn mutant animals. Furthermore, we show that the expression level of numerous regulators of neuromuscular junction formation, namely agrin, neuregulin-2 and TGF-ß receptor II, is downregulated in the spinal motor neurons of Hnf6 mutant newborn animals. Finally, altered formation of neuromuscular junction-like structures in a co-culture model of wildtype myotubes with mutant embryonic spinal cord slices is rescued by recombinant agrin and neuregulin, indicating that depletion in these factors contributes to defective neuromuscular junction development in the absence of HNF-6. Thus, HNF-6 controls in spinal motor neurons a genetic program that coordinates the formation of hindlimb neuromuscular junctions.